Association between caloric adequacy and short-term clinical outcomes in critically ill patients using a weight-based equation: Secondary analysis of a cluster-randomized controlled trial - Lv, Cheng; Jiang, Xingwei; Long, Yi; Liu, Zirui; Lin, Jiajia; Wu, Cuili; Ye, Xianghong; Ye, Ruiling; Liu, Yuxiu; Liu, Man; Liu, Yang; Chen, Wensong; et al. (Frontiers in Nutrition, 2022)
Background: There is controversy over the optimal energy delivery in intensive care units (ICUs). In this study, we aimed to evaluate the association between different caloric adequacy assessed by a weight-based equation and short-term clinical outcomes in a cohort of critically ill patients. Methods: This is a secondary analysis of a cluster-randomized controlled trial (N=2772). Energy requirement was estimated as 25 kcal/kg of body weight. The study subjects were divided into three groups according to their caloric adequacy as calculated by the mean energy delivered during day3 to day7 of enrollment divided by the estimated energy requirements: 1) received <70% of energy requirement (hypocaloric), 2) received 70%-100% of energy requirement (normocaloric), 3) received >100% of energy requirement (hypercaloric). Cox proportional hazards models were used to analyze association between caloric adequacy and 28-day mortality and time to discharge alive from the ICU. Results: A total of 1694 patients were included. Compared with normocaloric feeding, hypocaloric feeding significantly increased the risk of 28-day mortality (hazard ratio [HR] = 1.590, 95% confidence interval [CI]: 1.162-2.176, P = 0.004), while hypercaloric feeding did not. After controlling for potential confounders, the association remained valid (adjusted HR = 1.596, 95% CI: 1.150-2.215, P = 0.005). The caloric adequacy was not associated with time to discharge alive from the ICU in the unadjusted and the adjusted models. Conclusions: Energy delivery below 70% of estimated energy requirement during days 3-7 of critical illness is associated with 28-day mortality.